Late Mesozoic Structure and Evolution of the western Hammerfest Basin (SW Barents Sea) from 3 D Seismic Interpretation - Chaudry, Muhammad (2009)
In this study 2D and 3D seismic data has been interpreted in a study which covers the western parts of the Hammerfest Basin, in the south-western Barents Sea. The purpose of the thesis has been to study the Middle Jurassic to mid-Cretaceous evolution of this part of the Hammerfest Basin with an emphasis on the structural style and timing of the faulting. The interpreted horizons have identified from the information available from the formations tops in the wells 7120/6-1 and 7120/8-2. Though the formation tops in the wells and the horizons tops interpreted on seismic have misties, the seismic signatures of the horizons gives confidence in interpreting the data and in correlating the stratigraphic horizons in the wells and on the seismic. The seismic data interpretation has been carried out using PETREL. The seismic data quality is generally good and there was no difficulty in tracking and interpreting the seismic horizons. Four main reflectors were interpreted in the whole study area. The Top Stø Formation defines the late Middle Jurassic, the Top Hekkingen Formation defines the Base Cretaceous, the Top Knurr is considered as Lower Cretaceous and the Top Kolje as mid-Cretaceous (Barremian). Time-structure and time-thickness maps of all the four horizons have been made to see the structure and the fault pattern and thicknesses of the sequences in the area. For this purpose the fault synthesis has been performed on each horizon separately and finally a fault overlay map of all the horizons have been made to see the overall structural trend. The seismic interpretation of selected profiles has been done to see the timing of the structures and suggests us about the timing of the faults and the fault synthesis tells us about the overall structural trends in the area.